The use and effectiveness of rituximab maintenance in patients with follicular lymphoma diagnosed between 2004 and 2007 in the United States. Issue 12 (25th March 2014) - Nastoupil, Loretta J.; Sinha, Rajni; Byrtek, Michelle; Zhou, Xiaolei; Taylor, Michael D.; Friedberg, Jonathan W.; Link, Brian K.; Cerhan, James R.; Dawson, Keith; Flowers, Christopher R.
<x xml:space="preserve">Abstract</x> BACKGROUND The authors examined the "real‐world" effectiveness of rituximab (R) maintenance therapy (R‐maintenance) compared with observation after R‐based induction therapy in patients with previously untreated follicular lymphoma (FL) in the United States. METHODS The National LymphoCare Study is a prospective, multicenter, observational study that enrolled > 2700 untreated patients with FL diagnosed from 2004 to 2007 at 265 sites in the United States. Among these, patients who achieved at least stable disease after R‐based induction therapy were eligible for the current analysis. Patients who initiated R‐maintenance within 215 days of completing induction therapy were categorized as the R‐maintenance group, and those who did not initiate therapy during this period were categorized as the observation group. The objective of the current study was to determine the effect of R‐maintenance on progression‐free survival (PFS), time to next treatment (TTNT), and overall survival (OS). RESULTS A total of 1439 patients completed R‐based induction therapy, 1186 of whom met all inclusion criteria (541 patients received R‐maintenance and 645 patients were observed). Characteristics that were found to be predictive of receiving R‐maintenance were histology grade (1/2), Ann Arbor stage of disease (III/IV), geographic region (region other than the West), and practice setting (community practice). With a median follow‐up of 5.7 years, R‐maintenance was associated with superior PFS (hazards ratio [HR], 0.68; 95% confidence interval [95% CI], 0.56‐0.84 [P = .0003]) and TTNT (HR, 0.66; 95% CI, 0.52‐0.84 [P = .0007]). No significant difference in OS was observed (HR, 0.81; 95% CI, 0.58‐1.14 [P = .23]). CONCLUSIONS R‐maintenance in patients with FL and at least stable disease after R‐based induction therapy provided significantly longer PFS and TTNT in comparison with observation, but no significant difference in OS was observed with 5‐years of follow‐up. This comparative effectiveness study aligns with the results of randomized trials suggesting that similar outcomes occur with R‐maintenance in FL with the treatment variations observed in clinical practice. Cancer 2014;120:1830–1837. © 2014 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society.